PSIKOEDUKASI PADA PEMAIN FUTSAL UNTUK MENGATASI KETAKUTAN AKAN PENILAIAN NEGATIF (FEAR OF JUDGEMENT) KOMUNITAS FUTSAL DI SURABAYA - Emiliyanto Ivan Zulkarnain; Herlan Pratikto (PT. Hasba Edukasi Mandiri, 2025)
Futsal requires not only physical and technical readiness but also strong psychological preparedness, particularly in competitive situations involving social evaluation. One common psychological issue experienced by futsal players is fear of judgement, defined as anxiety related to negative evaluation by coaches, teammates, or spectators. This study aimed to describe the implementation of psychoeducation as an intervention to address fear of judgement among players of the OR Futsal Community in Surabaya. The study employed a qualitative approach with a community-based intervention design. Participants were active futsal players aged 18–25 years, selected using purposive sampling. Data were collected through participatory observation, semi-structured interviews, and Focus Group Discussions (FGD). The intervention consisted of three psychoeducational sessions focusing on understanding fear of judgement, strengthening emotional regulation in competitive contexts, and developing supportive team communication. The results indicated a reduction in evaluative anxiety, increased self-awareness, and improvements in emotional regulation and interpersonal communication among players. Psychoeducation was found to be an effective initial approach to fostering a psychologically safe environment and enhancing sustainable team performance.